Effects of Multiple Nonnative Fish on an Imperiled Cyprinid, Hornyhead Chub. Issue 6 (15th October 2019) - Hickerson, Brian T.; Maitland, Bryan M.; Walters, Annika W.
Abstract: Nonnative fish can have substantial negative effects on the abundance and distribution of native fishes through predation and competition. Nonnative predators are of particular interest because they represent novel threats to native prey species that are not adapted to their presence. Prey species with limited distributions or population sizes may be particularly vulnerable to the effects of nonnative predators. In the Laramie River, four nonnative predators—Brown Trout Salmo trutta, Rainbow Trout Oncorhynchus mykiss, Brook Trout Salvelinus fontinalis, and Smallmouth Bass Micropterus dolomieu are present along with a state‐imperiled population of Hornyhead Chub Nocomis biguttatus . The abundance of Hornyhead Chub has declined with increasing abundance of nonnative predators, with the probability of occurrence of Hornyhead Chub dropping drastically when Smallmouth Bass were present. All four nonnative species preyed on native cyprinids, but Smallmouth Bass relied most heavily on fish as a prey item. Isotopic niche overlap occurred between Hornyhead Chub and all of the nonnative predator species. Our results demonstrate that nonnative predators have the potential to negatively affect the abundance and distribution of Hornyhead Chub through the mechanisms of predation and competition, and predator identity is important in determining the extent of effects. Smallmouth Bass are a greater concern than nonnative salmonids because of their more piscivorous behavior, and their recent upstream expansion may be limiting the downstream distribution of Hornyhead Chub in the Laramie River.